Zadanie 1 Doprowadź wyrażenia do najprostszej postaci. Podaj konieczne założenia.

^ - do potęgi
* - razy

a. 8 * ( 3/4x - 1) + ( -15x^2 +5x) : ( -5x) -(-3x+2) * (-1)
b. -a * (1/4x - 5/8) + (16x^2 - 8x) : (-4x) + (-1) * ( 2+x)
c. -2(3-a-a^2) + 5(1+a-2a^2) - ( 9a^3 - 12a^2 - 3a) : ( -3a)
d. ( 12a^4b^4 - 9a^2b^3) : ( -3a^2b) - ( 2+3a^2b) * b^2

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T13:48:35+01:00
A. 8 * ( 3/4x - 1) + ( -15x^2 +5x) : ( -5x) -(-3x+2) * (-1)= 6x-8+3x-1-(3x-2)= 6x-8+3x-1-3x+2= 6x-7

b. -a * (1/4x - 5/8) + (16x^2 - 8x) : (-4x) + (-1) * ( 2+x)=
-1/4ax+5/8a -4x+2-2-x=-1/4ax+5/8a-5x


c. -2(3-a-a^2) + 5(1+a-2a^2) - ( 9a^3 - 12a^2 - 3a) : ( -3a)=
-6+2a+2a²+5+5a-10a²-(-3a²+4a+1)=-6+2a+2a²+5+5a-10a²+3a²-4a-1=-5a²+3a-2

d. ( 12a^4b^4 - 9a^2b^3) : ( -3a^2b) - ( 2+3a^2b) * b^2=-4a²b³+3b²-2b²-3a²b³= -7a²b³+b²
15 4 15